The association between cardiovascular health and obstructive sleep apnea symptoms: findings from NHANES - Guo, Qian; Dong, Dong; Zhou, Qiang; Huang, Shuman; Qiao, Xinjie; Dang, Zihan; Wang, Xiaowu; Zhao, Yulin (Frontiers in Cardiovascular Medicine, 2024)
ObjectiveTo investigate the association between cardiovascular health (CVH) and obstructive sleep apnea (OSA) within the U.S. population.MethodsThis study enrolled 12,540 participants aged 20 years and older from the 2007–2008 and 2015–2018 cycles of the National Health and Nutrition Examination Surveys (NHANES). Weighted univariate and multivariate logistic regression were utilized to examine the relationship between CVH and OSA symptoms. Life's Essential 8 (LE 8) metrics was employed to evaluate the CVH status of participants. Identification of OSA symptoms was determined based on a sleep questionnaire. They include (1) how often you snore; (2) how often you snort/stop breathing; or (3) how often you feel overly sleepy during day. Individuals who answered that they snore 3 or more per week; snort/stop breathing 3 or more per week and feel overly sleepy during day 16–30 times per month were classified as having OSA symptoms.ResultsSignificant inverse associations were observed between LE8 scores and symptoms of OSA after adjusting for covariates. The 95% CI was 0.750 (0.630,0.893) for the moderate CVH group and 0.573 (0.454,0.723) for the high CVH group. Subgroup analyses, stratified by age and gender, highlighted a significant interaction between LE8 scores and OSA symptoms with age (P < 0.0001). Participants under 60 years old in the high CVH group exhibited a reduced likelihood OSA symptoms (OR: 0.470; 95% CI: 0.345,0.641). Restricted cubic splines (RCS) in a multivariate regression analysis showed a non-linear relationship between LE8 score and OSA. Our finding demonstrates a substantial decrease in OSA symptom prevalence with increased LE 8 scores.ConclusionThe results demonstrate a strong inverse correlation between LE8 scores and OSA symptoms. Participants with higher LE8 scores showed a reduced likelihood of experiencing OSA symptoms.